Mengidentifikasi Metodologi Penelitian Inovatif yang Sesuai dengan Kompleksitas Komunikasi Bisnis di Era Digital - Meylania Chelsea Aghatta; Vanessa Koroh; Andi Muhammad Farhat; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The digital era demands innovative methodological approaches to address the complexity of business communication. This literature study analyzes the integration of Design Thinking (DT) with Integrated Marketing Communication (IMC) strategies and the development of inclusive information system evaluation models. The findings indicate that the human-centered synergy of DT and IMC is effective in creating product innovation, differentiation, and sustainable competitive advantage by leveraging digital platforms and analytical data. On the other hand, the development of evaluation models—such as the ICTRT framework—that expand technical perspectives by incorporating sociocultural dimensions, gender literacy, and ethical values proves crucial for strengthening accountability, compliance, and clean governance in digital business interactions. In conclusion, sustainable competitive advantage in the digital age requires a holistic approach that harmonizes human-centered creativity, technical robustness, regulatory compliance, and ethical principles within an integrated framework.